INTEGRATION OF ARTIFICIAL NEURAL NETWORKS FOR IDENTIFICATION OF COMPUTER SYSTEMS STATES - Pomorova, Oksana (International Journal of Computing, 2014)
The main principles of methodology of intellectualization computer systems diagnosing process are presented in paper.Offered the information model, method and means of computer systems states clusterization provide an opportunity of diagnosing on the basis of the incomplete diagnostic information. For identification of computer systems states are used the union of neural nets experts which are constructed with use of artificial neural networks architecture ART2 and SOM.